Application of composite structures in bridge engineering. Problems of construction process and strength analysis = Zastosowanie konstrukcji zespolonych w mostownictwie. Problemy konstrukcyjne i analiza wytrzymałościowa - Flaga, Kazimierz; Furtak, Kazimierz (1951- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Steel-concrete composite structures have been used in bridge engineering from decades. This is due to rational utilisation of the strength properties of the two materials. At the same time, the reinforced concrete (or prestressed) deck slab is more favourable than the orthotropic steel plate used in steel bridges (higher mass, better vibration damping, longer life).
Keywords: konstrukcje zespolone; płyta pomostu; most; pełzanie betonu; steel-concrete composite; structures bridge; bridge desk; shrinkage; creep of concrete